Long-term outcome, survival and predictors of mortality after MitraClip therapy: Results from the German Transcatheter Mitral Valve Interventions (TRAMI) registry - Kalbacher, Daniel; Bekeredjian, Raffi; Zahn, Ralf; Senges, Jochen (International journal of cardiology, 2019)
Background MitraClip therapy is increasingly used in patients deemed inoperable to treat severe mitral regurgitation (MR), but long-tern data is scarce. Aims The multicentre, industry-independent German Transcatheter Mitral Valve Interventions (TRAMI) registry comprises the largest prospectively enrolled cohort of patients treated by MitraClip therapy. The current analysis is focusing on long-term mortality rates, cardiac rehospitalization and reintervention. Methods and results Long-term follow-up (median time 1037days) in the TRAMI registry was available for 722 patients treated at 20 German centres. Improvements in New York Heart Association (NYHA) functional class (I/II long-term: 65% vs. 1-year follow-up: 63.3%) and self-rated health-status (EuroQuol visual analogue scale [EQ VAS] long-term: 60 [50-70] vs. 1-year follow-up: 60 [50; 70]) were pertained over time. Estimated mortality rates by Kaplan-Meier method were 19.7% for 1-year, 31.9% for 2-year and 53.1% for 4-year follow-up without differences found for MR aetiology. Multivariable Cox-regression analysis identified previous aortic valve implantation (hazard ratio [HR]=2.21; p<0.0001), NYHA class IV (HR=1.78; p<0.001), prior cardiac decompensation (HR=1.63; p<0.001), creatinine>1.5mg/dl (HR=1.63; p<0.0001) and left ventricular ejection fraction<30% (HR=1.60; p<0.001) as most predictive for long-term mortality. Conclusions Long-term outcome in the TRAMI registry confirmed lasting clinical improvements and low intervention rates. Long-term mortality was strongly influenced by cardiac and non-cardiac co-morbidities and was found comparable for both MR aetiologies.
Available online 10 August 2018
Gesehen am 15.02.2019